4-Amino-1,2,4-triazole-3-thione as a Promising Scaffold for the Inhibition of Serine and Metallo-β-Lactamases - Pasquale Linciano; Eleonora Gianquinto; Martina Montanari; Lorenzo Maso; Pierangelo Bellio; Esmeralda Cebrián-Sastre; Giuseppe Celenza; Jesús Blázquez; Laura Cendron; Francesca Spyrakis; Donatella Tondi (MDPI AG, 2020)
The emergence of bacteria that co-express serine- and metallo- carbapenemases is a threat to the efficacy of the available β-lactam antibiotic armamentarium. The 4-amino-1,2,4-triazole-3-thione scaffold has been selected as the starting chemical moiety in the design of a small library of β-Lactamase inhibitors (BLIs) with extended activity profiles. The synthesised compounds have been validated in vitro against class A serine β−Lactamase (SBLs) KPC-2 and class B1 metallo β−Lactamases (MBLs) VIM-1 and IMP-1. Of the synthesised derivatives, four compounds showed cross-class micromolar inhibition potency and therefore underwent in silico analyses to elucidate their binding mode within the catalytic pockets of serine- and metallo-BLs. Moreover, several members of the synthesised library have been evaluated, in combination with meropenem (MEM), against clinical strains that overexpress BLs for their ability to synergise carbapenems.